MCU encodes the pore conducting mitochondrial calcium currents - Chaudhuri, Dipayan (eLife Sciences Publications, Ltd, 2013)
Mitochondrial calcium (Ca(2+)) import is a well-described phenomenon regulating cell survival and ATP production. Of multiple pathways allowing such entry, the mitochondrial Ca(2+) uniporter is a highly Ca(2+)-selective channel complex encoded by several recently-discovered genes. However, the identity of the pore-forming subunit remains to be established, since knockdown of all the candidate uniporter genes inhibit Ca(2+) uptake in imaging assays, and reconstitution experiments have been equivocal. To definitively identify the channel, we use whole-mitoplast voltage-clamping, the technique that originally established the uniporter as a Ca(2+) channel. We show that RNAi-mediated knockdown of the mitochondrial calcium uniporter (MCU) gene reduces mitochondrial Ca(2+) current (I(MiCa)), whereas overexpression increases it. Additionally, a classic feature of I(MiCa), its sensitivity to ruthenium red inhibition, can be abolished by a point mutation in the putative pore domain without altering current magnitude. These analyses establish that MCU encodes the pore-forming subunit of the uniporter channel. DOI: http://dx.doi.org/10.7554/eLife.00704.001